Altered Cingulate Cortex Functional Connectivity in Normal Aging and Mild Cognitive Impairment - Cera, Nicoletta; Esposito, Roberto; Cieri, Filippo; Tartaro, Armando (Frontiers in Neuroscience, 2019)
Purpose: resting-state Functional Magnetic Resonance Imaging studies revealed that brain is organized into specialized networks constituted by regions that show a coherent fluctuation of spontaneous activity. Among these networks, the cingulate cortex appears to play a crucial role, particularly in the Default Mode Network, the Dorsal Attention Network and the Salience Network. In the present study we mapped the functional connectivity pattern of different regions of cingulate cortex: Anterior Cingulate Cortex, Mid Cingulate Cortex and Posterior Cingulate Cortex/Retro Splenial Cortex that have been in turn divided in a total of 9 sub regions. We compared functional connectivity patterns of the cingulate sub regions in a sample of Mild Cognitive Impairment patients and healthy elderly subjects. Methods: we enrolled 19 healthy elders (age range: 61–72 y.o.) and 16 Mild Cognitive Impairment patients (age range 64–87 y.o.), All participants had comparable levels of education (8–10 years) and were neurologically examined to exclude visual and motor impairments, major medical conditions, psychiatric or neurological disorders and consumption of psychotropic drugs. The diagnosis of Mild Cognitive Impairment has been performed according with Petersen criteria. Subjects were evaluated with Mini Mental State Examination, Frontal Assessment Battery, and prose memory (Babcock story) tests. In addition, with functional Magnetic Resonance Imaging, we investigated resting-state network activities. Results: healthy elderly, compared to Mild Cognitive Impairment, showed significant increased level of functional connectivity for the ventral part of Anterior Cingulate Cortex in correspondence of the bilateral caudate and Ventro Medial Pre Frontal Cortex. Moreover, for the Mid Cingulate Cortex the healthy elderly group showed increased levels of functional connectivity in somatomotor region, Pre Frontal Cortex, Superior Parietal Lobule. Whereas Mild Cognitive Impairment group, showed increased level of functional connectivity for the Superior frontal gyrus, frontal eye field and orbitofrontal cortex, compared to the healthy elderly group. Conclusion: our findings indicate that cognitive decline observed in Mild Cognitive Impairment patients damages the global functional connectivity of the cingulate cortex, supporting the idea that abnormalities in resting-state activities of the Cingulate Cortex could be a useful additional tool in order to better understand the brain mechanisms of the MCI.